(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Scenic script of the theatrical work "eXílio," produced by Coletivo Comum, a group based in São Paulo. The work, with text and direction by Fernando Kinas, premiered in April 2024 and had runs at Teatro de Contêiner and Teatro Arthur Azevedo.